Differential Molecular Diagnosis in Acute Myeloid Leukaemia: A Review - Ajayi O.I. , and Garba, N. * (Sokoto Journal of Medical Laboratory Science)
Acute myeloid leukemia (AML) is heterogeneous clonal disorders characterized by the production of immature and non-functional myeloid cells known as blasts and subsequently result in bone marrow failure and organs infiltrations. This review aims at presenting a detailed account on differential molecular diagnosis in acute myeloid leukemia. Specifically, the differential karyotype in AML and its prognostic importance are discussed. The review also focused on the current gene mutations on all forms of AML. Cytogenetically, AML is divided into two; AML with abnormal karyotype and AML with normal karyotype. Cytogenetics testing remains a critical diagnostic and prognostic marker in AML with abnormal karyotype. But conventional cytogenetics analysis cannot identify any chromosomal aberration in AML with normal karyotype. This is because, there are some chromosomal aberrations that are generally cryptic and cannot be identified by conventional cytogenetics (AML with normal karyotype). Advanced techniques such as Array comparative genomic hybridization (array CGH), Nano string technology and gene sequencing are usually used for the identification of those aberrations. Differential molecular diagnosis had provided good information for both diagnosis and prognosis of AML. Chromosomal aberrations such as t (8;21), t (15;17) and inv (16) or t (16;16) confirm the presence of AML regardless of the blasts count and are associated with favorable prognosis. A newly diagnosed patient with AML and a normal karyotype should be checked for more common mutations on genes like FLT3, NPM 1, CEBPA, RUNX1, MLL-PTD, or EVI 1, which may have prognostic and possibly therapeutic implications. We therefore, recommend that, researchers should discover the driving oncogenic events such as gene mutations or other aberrations in cytogenetically normal AML (CN-AML) which will help to find targets for the development of novel therapies and to determine prognostic factors for this group of patients.